1999
DOI: 10.1007/s003920050315
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Erfassung von Veränderungen der thorakalen Aorta bei Patienten mit chronischer Aortendissektion mittels transösophagealer Echokardiographie

Abstract: The aim of this serial 3 year follow-up study in 42 clinically stable patients with chronic aortic dissection was to assess quantitatively morphologic changes of the descending thoracic aorta (AD) using transesophageal echocardiography (TEE). Communicating dissections (ca) were present in 16/19 patients with operated type I and in 11/23 patients with type III AD whereas 12/23 type III AD according to De Bakey were non-communicating (nc). Diametral enlargement of the disc. thoracic aorta was 4 mm (mean value) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In most cases, patients with an underperforming thyroid are bradycardic 68,88 . Patients also have an increased incidence of hypercholesterolemia 87 and hypertriglyceridemia 89,90 . Patients have an increased low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), high-density lipoprotein (HDL) 89 and apolipoprotein B-71 (Apo B 71 ), and lipoprotein (a) (Lp[a] 92 ) and these cholesterol levels can be lowered in these patients by administration of TH therapy 93 .…”
Section: Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, patients with an underperforming thyroid are bradycardic 68,88 . Patients also have an increased incidence of hypercholesterolemia 87 and hypertriglyceridemia 89,90 . Patients have an increased low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), high-density lipoprotein (HDL) 89 and apolipoprotein B-71 (Apo B 71 ), and lipoprotein (a) (Lp[a] 92 ) and these cholesterol levels can be lowered in these patients by administration of TH therapy 93 .…”
Section: Hypothyroidismmentioning
confidence: 99%
“…Patients also have an increased incidence of hypercholesterolemia 87 and hypertriglyceridemia 89,90 . Patients have an increased low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), high-density lipoprotein (HDL) 89 and apolipoprotein B-71 (Apo B 71 ), and lipoprotein (a) (Lp[a] 92 ) and these cholesterol levels can be lowered in these patients by administration of TH therapy 93 . Patients suffering from subclinical hyperthyroidism have also shown diastolic and systolic dysfunction during exercise, resulting in impaired exercise tolerance in these them 95,96 .…”
Section: Hypothyroidismmentioning
confidence: 99%
“…Complete thrombosis of the false lumen was associated with an improved survival compared to apparent absence of thrombus formation [6]. Interestingly, this was related to the aortic diameter changes during follow-up since those with thrombus formation had an expansion rate in the range of < 3 mm, whereas those without thrombus formation had an expansion of > 9 mm during a 3-year follow-up period [7]. Richartz et al [8] recently showed that prognosis in patients with Stanford type A dissection is diverse and proposed patients to be subclassified into three groups according to the location of the entry site in the ascending aorta.…”
Section: Introductionmentioning
confidence: 99%